An Overview of Palm, Jatropha & Algae as a Potential Biodiesel Feedstock in Malaysia - Syarifah, Yunus; N. R., Abdullah; R., Mamat; A. A., Rashid (IOP Publishing, 2013)
The high demand to replace the petroleum fuel makes renewable and sustainable sources such as Palm oil, Jatropha oil and Algae as main focus feedstock for biodiesel production in Malaysia. There are many studies conducted on Palm oil and Jatropha oil, however, the use of Algae as an alternative fuel is still in its infancy. Malaysia already implemented B5 based Palm oil as a feedstock and this biodiesel has been proven safe and can be used without any engine modification. The use of biodiesel produced from these feedstock will also developed domestic economic and provide job opportunities especially in the rural area. In addition, biodiesel has many advantages especially when dealing with the emissions produce as compared to petroleum fuel such as; it can reduce unwanted gases and particulate matter harmful to the atmosphere and mankind. Thus, this paper gathered and examines the most prominent engine emission produced from Palm oil and Jatropha feedstock and also to observe the potential of Algae to be one of the sources of alternative fuel in Malaysia.